Improving Students’ Mathematical Creative Thinking and Resillience Using Eliciting Activities Approach - Susilawati, Lia; Afrilianto, M.; Sumarmo, Utari ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
The ability of students in mathematics especially in creative thinking and resillience is still low. This reseacrch aimed to overcome the low ability of students mathematical creative thinking and resillience using eliciting activites approach and also to analyze the role of model eliciting activities (MEAs) on students’ mathematical creative thinking (MCT) and mathematical resillience. The method used in this research is a qualitative-quantitative method with quasi-experimental control group design. Subjects of this research are 30 students of 11th grade which selected randomly from 4 classess majoring agribusiness and holticultura in SMKN 4 Padalarang. Instruments of this research are mathematical creative thinking test ability (MCTA), a mathematical resillience scale (MR), and a student’s opinion on MEAs. The results of this research found that students getting treatment with MEAs attained better grade on MCTA than the grades of students taught by sciencetific approach (SA) eventough both grades were still at low-medium level. On MR, there was no different grades between students on both teaching approaches, and those grades were at medium-fairly good level. Besides that, the research found that students realized some difficulties in solving MCTA tasks, and there was no association between MCTA and MR.  the facts found in this research concluded that the use of eliciting activities approach could improve the ability of students’ mathematical creative thinking and resilience.